Improvements to the Appointment of Regional Heads through Direct Elections from the Perspective of Article 18, Paragraph (4) of the 1945 Constitution - Zulwisman; Charles Simabura (Dinasti Research, 2026)
This study examines the constitutional ambiguity of Article 18, paragraph (4) of the 1945 Constitution of the Republic of Indonesia regarding the phrase “elected democratically,” which serves as the legal basis for regional elections in Indonesia. Although regulations have evolved through Law No. 10 of 2016 to strengthen popular sovereignty, the practice of direct regional elections has instead become trapped in a “democratic pathology” characterized by 82% dominance by capital (financiers) and TSM (Structured, Systematic, and Massive) fraud. This phenomenon results in popular sovereignty being hijacked by transactional interests. Using a legal-normative approach, this study asserts that the sole solution to safeguard the integrity of local leadership appointments lies in reconstructing the oversight model. The integration of strengthened Bawaslu authority with the digitization of participatory oversight (Gowaslu) and community cadre development (SKPP) is an absolute prerequisite for restoring the dignity of elections in alignment with the principles of deliberation and representation.